Current Status and Utilization of Oral and Dental Health Services in Gezira State (2005-2009) - Yousif, Mogahid Abd El Rahman; A. Ghandour, Ibrahim; A. Idris, Ali; Mahfouz, Mohamed (Gezira Journal of Health Sciences, 2015)
Objective:   This study aimed to assess the status of the present dental and oral health services   in the Gezira state.  Methods : The study areas comprise of three clusters: urban, suburban and rural. Five study sites in the urban area, four sites in suburban area around Wad Medani and 12 sites in the rural area were chosen from the six localities of Gezira State . The households study sample was as follows: 100 in the urban area, 108 in the rural area and 52 in the suburban area. The study tools were direct pre-coded questionnaires, household survey and observation checklist. The procedure involved household interview to evaluate dental  status of dental health professionals, equipment and materials in order to assess dental health services. Descriptive statistics was used to analyze and present the data. The SPSS Statistical Programme using Microsoft Windows was used. Results: This result revealed absolute lack of dental services in the rural and relative lack of services in suburban areas. The present unit is old and most of them were incomplete and not functioning. This was the reason that some of rural and suburban populations seek oral health services in Wad Medani health institutions. Most of the patients irrespective of their residence preferred treatment at private dental clinics because they expect better care due to good facilities Recommendation: Establishing new dental units with good facilities distributed in different localities and rehabilitation of dental units provided to Elhasaheisa and Elmanagil dental departments with equipments and dental specialties to become specialized dental hospitals to cover the population needs and demand dental services for the surrounding areas.